(untitled) - Paltridge, Brian (New York, 2012)
This engagingly written introduction to discourse analysis is essential for students encountering discourse analysis for the first time, whether at undergraduate or postgraduate level. It should be on every reading list.
Phân tích diễn ngôn trong giảng dạy ngôn ngữ
Keywords: Discourse analysis,Phân tích diễn ngôn